(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the theoretical and practical aspects of applying Artificial Intelligence (AI) technologies in artistic gymnastics. It explores the digitalization of the training process, biomechanical analysis, video analytics, machine learning algorithms, and the prospects for using intelligent sensor systems to enhance athletic performance. In addition, based on international scientific research, the study analyzes the significance of AI technologies in improving athletes’ preparation, refining technical skills, optimizing training processes, and preventing sports-related injuries.